A well-preserved bimodal Archaean volcanic succession in the Tasiusarsuaq terrane, South-West Greenland - Stendal, Henrik; Scherstén, Anders ; 0000-0002-2105-6172 (GEUS Bulletin, 2007)
During the field campaign in the Nuuk region, one of the objectives was to describe Archaean primary geological environments (Hollis et al. 2006). On Nunatak 1390, which is part of the Tasiusarsuaq terrane (Figs 1, 2), a bimodal volcanic succession is preserved and interpreted as former ocean floor. The field investigation included geological mapping and sampling of the volcanic sequence comprising mafic to ultramafic rocks, and associated acid volcanic rocks and granite intrusions.